Is there a role for surgery in stage ⅢA-N2 non-small cell lung cancer? - Paul E. VAN SCHIL; Michèle DE WAELE; Jeroen M. HENDRIKS; Patrick R. LAUWERS (Chinese Journal of Lung Cancer, 2008)
The role of surgery in stage ⅢA-N2 non-small cell lung cancer (NSCLC) remains controversial. Most important prognostic factors are mediastinal downstaging and complete surgical resection. Different restaging techniques exist to evaluate response after induction therapy and these are subdivided into non-invasive, invasive and alternative or minimally invasive techniques. In contrast to imaging or functional studies, remediastinoscopy provides pathological evidence of response after induction therapy. Although technically more challenging than a first procedure, remediastinoscopy can select patients for subsequent thoracotomy and provides prognostic information. An alternative approach consists of the use of minimally invasive staging procedures as endobronchial or endoscopic esophageal ultrasound to obtain an initial proof of mediastinal nodal involvement. Mediastinoscopy is subsequently performed after induction therapy to evaluate response. In this way, a technically more difficult remediastinoscopy can be avoided. Stage ⅢA-N2 NSCLC represents a heterogenous spectrum of locally advanced disease and different subsets exist. When N2 disease is discovered during thoracotomy after negative, careful preoperative staging a resection should be performed if this can be complete. Postoperative radiotherapy will decrease local recurrence rate but not overall survival. Adjuvant chemotherapy increases survival and is presently recommended in these cases. Most patients with pathologically proven N2 disease detected during preoperative work-up will be treated by induction therapy followed by surgery or radiotherapy.In two large, recently completed, phase Ⅲ trials there was no difference in overall survival between the surgical and radiotherapy arm, but in one trial there was a difference in progression-free survival in favor of the surgical arm. In the surgery arm the rate of local recurrences was also lower in both trials. Surgical resection may be recommended in those patients with proven mediastinal downstaging after induction therapy who can preferentially be treated by lobectomy. Pneumonectomy has a significantly higher mortality and morbidity rate, especially after induction chemoradiotherapy. Patients with bulky N2 disease are mostly treated with combined chemoradiotherapy although the precise treatment scheme has not been determined yet.